2012
DOI: 10.1177/155892501200700217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrospinning Setup and Process Parameters on Nanofiber Morphology Intended for the Modification of Quartz Crystal Microbalance Surfaces

Abstract: To improve the performance of mass sensitive biosensors, the surface of a piezoelectric quartz crystal transducer, is expanded by employing electrospun nanofibers to its surface. This work describes the effect of vertical-horizontal electrospinning setups and electrospinning parameters on fiber morphology. The research objective was to obtain finer and non-beaded fiber morphologies, via controllable and repeatable process parameters, for further applications of QCM surfaces in high performance DNA-, Aptamer-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 12 publications
0
60
0
3
Order By: Relevance
“…Process conditions such as applied voltage, flow rate and distance from needle to collector affect the morphology of fibers. Ding et al reported that average diameter of poly(vinyl alcohol) (PVA) fibers are slightly decreased with increasing the voltage, by study average diameter as a function of voltage at conditions (concentration = 11% and needle-collector distance = 8 cm) [61]. Rodoplu and Mutlu reported that when other parameters are kept constant and voltage increased, PVA nanofiber diameter decreases.…”
Section: Parameters Which Effect On the Morphology Of Nanofibers Prodmentioning
confidence: 99%
“…Process conditions such as applied voltage, flow rate and distance from needle to collector affect the morphology of fibers. Ding et al reported that average diameter of poly(vinyl alcohol) (PVA) fibers are slightly decreased with increasing the voltage, by study average diameter as a function of voltage at conditions (concentration = 11% and needle-collector distance = 8 cm) [61]. Rodoplu and Mutlu reported that when other parameters are kept constant and voltage increased, PVA nanofiber diameter decreases.…”
Section: Parameters Which Effect On the Morphology Of Nanofibers Prodmentioning
confidence: 99%
“…However, different ways for controlling the process temperature were reported. Temperature-controlled electrospinning can thus refer to heating only the syringe/polymer solution dispensing system [8,12], the collector [14] or the whole enclosure of the device [7,11,13]. This last approach is particularly relevant since it avoids the formation of temperature gradients which can interfere with the fiber formation process.…”
Section: Introductionmentioning
confidence: 98%
“…However, while producing nanofibers, the environmental conditions (temperature and relative humidity) are strongly influencing the obtained fiber morphology [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Many researchers have extensively studied the effects of these parameters in various studies. Parameters in each category affect the morphology of the fibers.…”
Section: Elkakaby Etkelmentioning
confidence: 99%